Putte di Coro and Venetian Talented Education in the Late 17th and Early 18th Centuries - Federica Gualdaroni; Andrea Mattia Marcelli (Pensa MultiMedia, 2023)
La Clotilde overo la Francia convertita by Coli Lucchese (1686) and Clotilde by Piccioli (1688) represent the two extremes of the continuum of female musical education in late 17th-century Venice. The first is a prose piece intended for a convent of former prostitutes, while the second is written for the "putte di coro," that is, the female musicians trained in the Ospedali of the city, which housed various categories of disadvantaged young girls. Primary sources reveal a contradictory narrative from the general public and visitors of that time, who were intrigued both by the ideal of purity represented by nuns and female pupils and by the possibility of breaking into their well-regulated lives. Nevertheless, the hermeneutics of the opera Le Amazoni nell'Isole Fortunate (Piccioli, 1679), organized by Marco Contarini in his villa in Terraferma, places the girls from the Ospedali within a framework perpetuating the patrician hegemony through control over representations. This study demonstrates the multiple educational implications of this framework: the construction of a Venetian national consciousness, the creation of the foreign myth of Italy as a land of music and mystery, the successful social integration of disadvantaged girls, the establishment of a pedagogical model and professionalization of musical talent, and finally, opportunities for the Maestri of the "cori" to experiment in their art.